The Development of Powerpoint-Assisted Algebra Learning Media to Increase Students’ Mathematical Communication Ability on Junior High School - Harisah, Iis; Anita, Ika Wahyu; Rohaeti, Euis Eti (IKIP Siliwangi, 2024)
The matter of algebraic form is crucial to study because the matter of the algebraical form is not only related to other mathematical matters but also related to everyday life, but there are still many students who have difficulty in communicating the explanation of the origin of the algebraic form. This is because the learning media used by the teacher is not interactive, so it affects the student's understanding and communication skills. For this reason, the study aims to cultivate the interest in learning and cultivate students' mathematical communication skills by developing algebraic learning media supported by a PowerPoint application. The method used in this research is research and development, with the development of a modified 4-D model in three stages namely determining, designing, and developing. The tool used to measure the quality of the learning media is a validation questionnaire for measuring the validity and student response to strengthen practicality. The results of this study show that the quality of the learning media meets the valid criteria with an overall average score of 79% and From the test carried out against students obtained an average scoring of 76%. Thus, the development of algebra learning media supported by the PowerPoint application has good quality and can be used in mathematical learning.